1988
DOI: 10.3758/bf03334873
|View full text |Cite
|
Sign up to set email alerts
|

The quantity, not the quality, of affect predicts memory vividness

Abstract: Vivid or detailed memories are reliably associated with the recollection of emotional events. However, the mechanism through which emotionality has this impact remains unspecified. Our results indicate that the character of the emotion does not influence memory vividness; instead, vividness seems to be dependent only on the quantity of emotion that accompanies the event.We consider the implications of this for accounts of emotion 's effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 20 publications
5
50
3
Order By: Relevance
“…This conclusion was supported by evidence that (a) larger proportions of R responses were given to more highly arousing, negative, and to a lesser extent, positive stimuli and (b) estimates of the contribution to performance of a consciously mediated recollection process (Yonelinas et al, 1998) produced the same pattern of results. These data provide initial support for the hypothesis that affect leads to increases in the distinctiveness with which stimuli are encoded and reexperienced in memory later .on and suggests that previous failures (Bradley et al, 1992;Reisberg et al, 1988) to detect an impact of valence on memory may have been due to the use of memory measures that were not sensitive to differences in the experience or process of recognizing past events.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This conclusion was supported by evidence that (a) larger proportions of R responses were given to more highly arousing, negative, and to a lesser extent, positive stimuli and (b) estimates of the contribution to performance of a consciously mediated recollection process (Yonelinas et al, 1998) produced the same pattern of results. These data provide initial support for the hypothesis that affect leads to increases in the distinctiveness with which stimuli are encoded and reexperienced in memory later .on and suggests that previous failures (Bradley et al, 1992;Reisberg et al, 1988) to detect an impact of valence on memory may have been due to the use of memory measures that were not sensitive to differences in the experience or process of recognizing past events.…”
Section: Discussionsupporting
confidence: 55%
“…Third, some previous failures to find effects of valence on memory have used recall rather than recognition tests (e.g., Reisberg et al, 1988;Thomas & Diener, 1990). Recall tests either may not present retrieval cues strong enough to elicit differences in phenomenal experience between negative and positive items or they may not use measures (e.g., rating vividness) that are sensitive enough to detect differences in this experience.…”
Section: Implications For Other Findings and Memory Phenomenamentioning
confidence: 99%
“…In contrast, emotion undermined memory for details not associated with the event's center. The mechanisms for emotion's effects are discussed.The emotional events in one's life tend to be remembered with great clarity and detail (e.g., Bohannon, 1988; Brown & Kulik, 1977;Pillemer, 1984;Reisberg, Heuer, McLean, & O'Shaughnessy, 1988;Rubin & Kozin, 1984;White, 1989). But how accurate are these memories?…”
mentioning
confidence: 99%
“…Emotional valence can also influence memory by increasing attention and controlled processes during encoding mediated by frontal cortices (Kensinger & Corkin, 2004), but there is less evidence about the effects of valence during retrieval in LM studies, perhaps because of difficulty in equating the arousal associated with positive and negative memories. Consistent with the influence of emotion on LM, AMs that are more arousing (Reisberg, Heuer, McLean, & O'Shaugnessy, 1988;Talarico, LaBar, & Rubin, 2004) AM retrieval is influenced by emotional intensity. For example, found that the emotional intensity associated with AM retrieval modulated activity in the hippocampus, although amygdala activity was not directly observed.…”
Section: Emotionmentioning
confidence: 56%